Energy structure evaluation and optimization in BRICS: A dynamic analysis based on a slack based measurement DEA with undesirable outputs. (1st February 2021) - Sun, Shufen; Huang, Chenchen
Abstract: Improving the energy efficiency of emerging economies is the core of achieving efficient global development. This paper innovatively applies the slack based DEA to analyze the energy structure and energy-saving potential of BRICS countries in the past three decades. The results of empirical analysis show that, first, Brazil and Russia ranked first and last with the average efficiency of 0.5941 and 0.0921 respectively in the 30-year observation period. Second, the slack variable of each country is very large. For example, in 2018, India needs to reduce 436.17 Mtoe coal consumption, 105.65 Mtoe oil consumption, 25.39 Mtoe natural gas consumption, and 2038.05 million tons of carbon emissions to reach an effective state. Third, the reasons for inefficiency vary from country to country. Brazil, Russia, and India have low levels of energy management and lack of advanced key technologies. China and South Africa are faced with the problems of scale diseconomy and unreasonable resource allocation structure. The research results are helpful to understand the changing trend of energy efficiency and the reasons for low efficiency in BRICS, and can provide a reference for the formulation of scientific development strategy, which has important practical significance. Graphical abstract: Image 1 Highlights: Russia ranks last among the BRICS countries with an average efficiency of 0.0921. The highest average efficiency is found in Brazil at 0.5941. Brazil, Russia, and India lack of advanced key technologies. China and South Africa are facing the problems of diseconomy of scale.